Scintigraphic evaluation of bone formation in Göttingen minipigs: technical report - Schwarz, Markus; Seidling, Roland; Mauermann, Eckhard; Werner, A.; Steil, Volker; Forsch, Elmar; Obertacke, Udo; Becker, Kristianna; Lehmann, Lars (Scandinavian journal of laboratory animal science, 2010)
In experiments and processes requiring the application of nuclear tracers in large animals, statutory provisions and safety standards as well as a variety of techniques have to be regarded and employed. In order to sufficiently analyze questions pertaining to osseointegration as well as the possibility of ectopic bone formation in Göttingen minipigs, we decided to use scintigraphic examinations using 99mTc-HDP (Technetium - hydroxymethane diphosphonate). In this study, metallic implants coated in different forms with rhBMP-2 (recombinant human bone morphogenetic protein-2) were surgically introduced into the pigs’ femora. A total of 26 adult female minipigs (Ellegard, Dalmose, Denmark) averaging 40 months in age were post-surgically evaluated through the application of a radionuclide and its subsequent distribution using a scintillation camera. Each animal received approximately 10 MBq/kg BW (mega Becquerel per kilogram bodyweight). This paper describes the procedures of anaesthesia, the quite challenging transvaginal- urethral catheterization, the application of a catheter in the jugular vein, the radionuclide injection and the disposal of the sacrificed animals under statutory provisions and safety standards. The technical report reveals that the scintigraphic evaluation in large animal experiments is a practicable - yet sophisticated - method of examination and also strives to encourage further research groups to implement this elegant procedure.
Gesehen am 06.07.2023